Piezoelectric materials and devices : applications in engineering and medical sciences - Vijaya, M. S. (CRC Press, 2013)
"Starting from the fundamentals, this book provides a concise yet complete treatment of piezoelectric materials, an important class of smart materials which are useful as both actuators and sensors. Including case studies, the text introduces different types of dieleetric materials, describes the preparation and properties of various piezoelectric materials used in device applications, and presents various engineering and medical applications of piezoelectric materials. It also discusses in detail the design and virtual prototyping of piezoelectric devices using commercially available software tools like ANSYS and PAFEC"--